Aktivnosti kulturno prosvetnega društva Slovenski dom "Bazovica" v reškem tisku - Riman, Barbara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
ACTIVITIES OF THE CULTURAL AND EDUCATIONAL ASSOCIATION SLOVENE CENTRE BAZOVICA AS REPORTED IN RIJEKA PAPERS NOVI LIST AND LA VOCE DEL POPOLO FROM 1947 TO 1957. The article brings data on the founding of the CEA Slovene Centre Bazovica and its activities from 1947 to 1957 as reported in the Rijeka papers Novi list and La voce del popolo. It provides a comparative analysis of data based upon chronicles written since 1953, and an interpretation of data acquired from news, reports, viewpoints and critiques, which were published with varying intensity. The conclusion is that events concerning the CEA were followed irregularly, as were events concerning other minority communities in Rijeka and its territory. The research study has shown that newspaper articles can be a relevant comparative source for the study of the activities of the Slovene minority, and indirectly also of the status and daily life of Slovenes in Rijeka.
Keywords: Reka; Novi list; časopisi; Slovenci; Slovenes; kulturna društva; Hrvaška; Croatia; 1947/1957